56. Video-Conferencing with Audio Software - Baggaley, Jon; Klaas, Jim (International Review of Research in Open and Distributed Learning, 2006)
An online conference is illustrated using the format of a TV talk show. The conference combined live audio discussion with visual images spontaneously selected by the moderator in the manner of a TV control-room director. A combination of inexpensive online collaborative tools was used for the event, based on the browser-based audio-conferencing software, iVocalize. The exercise illustrates how an impression of a fully featured online video-conference can be created without the need for complex video-conferencing software and high bandwidth.